The johns hopkins manual of gynecology and obstetrics - Chou, Betty; Ovid Technologies, Inc. (Philadelphia : Wolters Kluwer, 2020)
'The Johns Hopkins Manual of Gynecology and Obstetrics is a trusted on-the-spot reference for virtually any situation in obstetrics, high-risk obstetrics, gynecology, reproductive endocrinology, infertility, and gynecologic oncology. It's also highly effective as a review tool for certification or re-certification exams'--
Electronic reproduction.
Keywords: Obstetrics; Genital Diseases, Female; Pregnancy Complications; Women's Health; Handbooks; Obstetrics; Generative organs, Female -- Handbooks, manuals, etc; Pregnancy complications -- Handbooks, manuals, etc